HUBUNGAN UMUR DAN PARITAS IBU HAMIL TRIMESTER III DENGAN KEJADIAN ANEMIA DI KABUPATEN KOTAWARINGIN TIMUR - Fitriana Nugraheni (STIKes Mitra Keluarga, 2023)
Anaemia causes a high maternal mortality rate due to lack of consumption of pregnant women and other factors such as age and parity. This research aims to identify the association with age and parity with anaemia during pregnancy. This research used purposive random sampling with a number of samples was 79 third trimester pregnant women. This research used the secondary data of the characteristics, HB levels, parity and age of respondent in Kotawaringin Timur Regency. This study showed that 70.9% of respondent had anaemia. Meanwhile, the frequency of parity >3 times and age at risk of anemia is 92.9% and 66.7%, respectively. The results showed there was a significant association between parity and anaemia (p 0.000; OR 4.003) and no association between age and anaemia (p 0.09). This study shows that parity >3 times has an association with the incidence of anaemia during pregnancy.